2014
DOI: 10.1016/j.febslet.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Gap junction and hemichannel‐independent actions of connexins on cell and tissue functions – An update

Abstract: Connexins, a family of transmembrane proteins, are components of both gap junction channels and hemichannels, which mediate the exchange of ions and small molecules between adjacent cells, and between the inside and outside of the cell, respectively. Substantial advancements have been made in the comprehension of the role of gap junctions and hemichannels in coordinating cellular events. In recent years, a plethora of studies demonstrate a role of connexin proteins in the regulation of tissue homeostasis that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
126
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(130 citation statements)
references
References 60 publications
(122 reference statements)
4
126
0
Order By: Relevance
“…In agreement with this possibility, the GLT current evoked in Cx30 -/-astrocytes by and tumorigenicity by interacting with a plethora of connexin-associated proteins including cytoskeletal elements, enzymes (kinases and phosphatases), adhesion molecules, and signaling molecules [7] . Consequently, Interestingly, Cx30 has been shown to interact with cytoskeletal proteins that regulate cell adhesion and motility [8] .…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…In agreement with this possibility, the GLT current evoked in Cx30 -/-astrocytes by and tumorigenicity by interacting with a plethora of connexin-associated proteins including cytoskeletal elements, enzymes (kinases and phosphatases), adhesion molecules, and signaling molecules [7] . Consequently, Interestingly, Cx30 has been shown to interact with cytoskeletal proteins that regulate cell adhesion and motility [8] .…”
mentioning
confidence: 54%
“…Histological studies indicated important morphological changes in astrocytes from Cx30 -/-mice. Although the role of the C-terminal tail of connexins in the regulation of cell morphology has been described, mainly in the context of cell adhesion, migration, and proliferation during disease and cancer development [7] , this study is the fi rst to demonstrate its role in a physiological process.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Gap junctions (GJs) are involved in direct signal transduction between adhering adjacent blastomeres. Gap junction intercellular communication (GJIC) transmits various signals including activation of the Hippo signaling pathway, which is associated with differentiation of the trophectoderm (TE) / inner cell mass (ICM) [3]. GJs have also been suggested to play a role in blastocoel formation of the preimplantation embryo [4].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the cellular functions of Cxs were attributed exclusively to direct cell-to-cell diffusion; however, some Cx functions seem to be independent of channel function (18). In fact, several reports have suggested that the Cx43 complex might fulfil functions that are not necessarily related to the control of GJIC.…”
mentioning
confidence: 99%